The Chimarra of the georgensis and fallax species groups in Madagascar (Trichoptera, Philopotamidae). (3rd April 2018) - Gibon, Francois-Marie
Abstract: Chimarra zombitsei sp. nov. is described from Madagascar. It belongs to the georgensis species group, described by Blahnik et al. (2012) and recorded here for the first time from Madagascar. A preliminary list of the Afrotropical species belonging to the group is given. The fallax species group is newly described and a preliminary species list for the group is given. The male genitalia of the holotype of Chimarra dybowskina Navás, 1931 are described for the first time and the species distribution on Madagascar is briefly exposed. Chimarra lukawei Jacquemart, 1961 is reported for the first time from the country; its distribution is briefly exposed. http://www.zoobank.org/urn:lsid:zoobank.org:pub:9004A4F3-9B7B-483D-8D41-04E92640E35C